The high-mobility group transcription factor Sox10 interacts with the N-myc interacting protein Nmi. - Wegner, Michael; et al. (Journal of Molecular Biology, 2005)
The high-mobility group transcription factor Sox10 exerts many different roles during development of the neural crest and nervous system. To unravel its complex transcriptional functions, we have started to look for interaction partners. Here, we identify an association of Sox10 with the N-myc interactor Nmi, which was mediated by the high-mobility group of Sox10 and the central region of Nmi. In vivo relevance of this interaction is indicated by the fact that both proteins were co-expressed in glial cells, gliomas and in the spinal cord. Additionally, subcellular localization of Nmi in C6 glioma depended on the presence of Sox10 such that nuclear Nmi was more frequent in Sox10-expressing cells. Importantly, Nmi modulated the transcriptional activity of Sox10 in reporter gene assays. Nmi effects varied between different Sox10 target gene promoters, indicating that Nmi function in vivo may be promoter-specific. © 2005 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2005.med.IB.LPCIPDBI.thehig_4
Keywords: Glia; HMG; Sox; Sry; Transcriptional co-activator